Surgical technique modifies the postoperative atrioventricular block rate in sutureless prostheses - Barbeito, Miguel González; Estévez-Cid, Francisco; Martínez, Patricia Pardo; de Sierra, Carlos Velasco García; Gil, Carmen Iglesias; Laguillo, Cristina Quiñones; Castillo, José Joaquín Cuenca (Journal of Thoracic Disease, 2019)
Background: The main objective was to analyse the impact of the modification of the Perceval S implantation technique on the prevalence of postoperative atrioventricular block, which requires a permanent pacemaker, in our aortic valve replacement series. In addition, we attempted to identify those risk factors that are related to the appearance of this complication. Methods: Five hundred and seventy-two valve replacements were carried out with PERCEVAL S in our centre up to July 2018. Use of modified technique (n=302). Minimally invasive approach (n=340). Associated coronary surgery (n=95). Patients with pacemakers prior to surgery (n=27) and associated mitral or tricuspid valve surgery (n=26) were excluded. We analysed variables of interest that could influence the increase in postoperative atrioventricular block. Technique performed, disorders of intraventricular conduction and pre/intraoperative characteristics. The influence of the modified technique was analysed. Results: Five hundred and nineteen aortic valve replacements with PERCEVAL S. Age (years) (median 77, interquartile range 8). Height (cm) (159, 13.5). Euroscore II (%) (2.25, 2.27). Postoperative atrioventricular block standard technique (n=23, 10.14%). Modified technique (n=14, 4.30%) (P=0.009). Multivariate regression analysis. Final model AUC =0.740, maximum model AUC =0.774 (P>0.05). Includes: Technique used (P=0.024), height (P=0.043) and disorders of interventricular conduction, right bundle branch block (P=0.005), trifascicular block (P=0.008). Conclusions: In our experience, the modified technique significantly decreases the incidence of postoperative atrioventricular block that requires a permanent pacemaker in the aortic valve replacement with PERCEVAL S. The prior electrocardiographic presence of right bundle branch block, trifascicular block and the height of the patient are associated with an increased risk of blocking.